In vivo X-Nuclear MRS Imaging Methods for Quantitative Assessment of Neuroenergetic Biomarkers in Studying Brain Function and Aging - Zhu, Xiao-Hong; Chen, Wei (Frontiers in Aging Neuroscience, 2018)
Brain relies on glucose and oxygen metabolisms to generate biochemical energy in the form of adenosine triphosphate (ATP) for supporting electrophysiological activities and neural signaling under resting or working state. Aging is associated with declined mitochondrial functionality and decreased cerebral energy metabolism, and thus, is a major risk factor in developing neurodegenerative diseases including Alzheimer’s disease (AD). However, there is an unmet need in the development of novel neuroimaging tools and sensitive biomarkers for detecting abnormal energy metabolism and impaired mitochondrial function, especially in an early stage of the neurodegenerative diseases. Recent advancements in developing multimodal high-field in vivo X-nuclear (e.g., 2H, 17O and 31P) MRS imaging techniques have shown promise for quantitative and noninvasive measurement of fundamental cerebral metabolic rates of glucose and oxygen consumption, ATP production as well as NAD redox state in preclinical animal and human brains. These metabolic neuroimaging measurements could provide new insights and quantitative bioenergetic markers associated with aging processing and neurodegeneration and can therefore be employed to monitor disease progression and determine effectiveness of therapeutic intervention.